دراسة تحليلية لمبدأ العدالة والالتزام في القانون الدولي العام - صالح، عبد السلام (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
There is no doubt that the principles of justice are the principles upon which all human ‎beings agree whatever their different forms, colors and beliefs. The criterion of ‎urbanization among human beings is measured by the extent to which the systems of ‎political states adhere to the principles of justice. The international community, ‎especially after the Second World War and its subsequent disasters on humanity, has ‎achieved many achievements in the provision of many rights and principles concerning ‎human rights and public freedoms, whether enshrined in international human rights law ‎or in international humanitarian law. Perhaps the clearest picture of these innate rights ‎that emerged from the rules of natural justice is the rights enshrined in the International ‎Covenants on Human Rights; the International Covenant on Political and Economic ‎Rights, and the International Covenant on Social and Cultural Rights. Through the ‎inspection of previous studies and the observation of the current reality, should activate ‎the commitment of States to implement United Nations resolutions, especially those ‎relating to international peace and security and activate the obligation of States to give ‎their citizens the rights contained in the International Covenants and other international ‎conventions provided for in the relevant conventions. Also to activate and improve the ‎work of the International Criminal Court to be apply to all war crimes and crimes ‎against humanity in various countries of the world without requiring that the State has ‎been signed on the Rome Convention establishing the Court.‎